2011
DOI: 10.1007/s00253-011-3235-1
|View full text |Cite
|
Sign up to set email alerts
|

High-yield production of hydrophobins RodA and RodB from Aspergillus fumigatus in Pichia pastoris

Abstract: Hydrophobins are small fungal proteins with amphipatic properties and the ability to self-assemble on a hydrophobic/hydrophilic interface; thus, many technical applications for hydrophobins have been suggested. The pathogenic fungus Aspergillus fumigatus expresses the hydrophobins RodA and RodB on the surface of its conidia. RodA is known to be of importance to the pathogenesis of the fungus, while the biological role of RodB is currently unknown. Here, we report the successful expression of both hydrophobins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 23 publications
3
21
0
Order By: Relevance
“…These differences are exacerbated in the case of the 3‐copy‐HFBI group, where PDI1 coexpression resulted in 7.8±0.2 fold increase, and ERO1 coexpression resulted in 30±4.0 fold increase relative to the 1‐copy‐HFBI/no chaperone strain, with each 3‐copy‐HFBI/chaperone coexpressing strain being statistically significant compared with the 3‐copy‐HFBI/no chaperone parent strain. The approximately 30‐fold increase in HFBI secretion for the 3‐copy‐HFBI/Ero1p strain corresponded to a production level of approximately 330 mg/L in the 5 ml scale used in this study, which is in the same range as previously reported production levels for class I hydrophobins RodA and RodB produced in a bioreactor under optimized conditions (Pedersen et al, ), and for purified HFBI produced in shake flasks (Lohrasbi‐Nejad et al, ). Statistical comparison for the effect of HFBI gene copy number on HFBI expression across groups is presented in Table .…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…These differences are exacerbated in the case of the 3‐copy‐HFBI group, where PDI1 coexpression resulted in 7.8±0.2 fold increase, and ERO1 coexpression resulted in 30±4.0 fold increase relative to the 1‐copy‐HFBI/no chaperone strain, with each 3‐copy‐HFBI/chaperone coexpressing strain being statistically significant compared with the 3‐copy‐HFBI/no chaperone parent strain. The approximately 30‐fold increase in HFBI secretion for the 3‐copy‐HFBI/Ero1p strain corresponded to a production level of approximately 330 mg/L in the 5 ml scale used in this study, which is in the same range as previously reported production levels for class I hydrophobins RodA and RodB produced in a bioreactor under optimized conditions (Pedersen et al, ), and for purified HFBI produced in shake flasks (Lohrasbi‐Nejad et al, ). Statistical comparison for the effect of HFBI gene copy number on HFBI expression across groups is presented in Table .…”
Section: Resultssupporting
confidence: 85%
“…Eukaryotic expression hosts such as yeasts have produced overall higher hydrophobin yields in a folded state. In particular, the methylotropic yeast Pichia pastoris as a heterologous host for recombinant hydrophobin production has been relatively successful in producing recombinant hydrophobins, with yields on the order of hundreds of milligrams per liter (Lohrasbi‐Nejad, Torkzadeh‐Mahani, & Hosseinkhani, ; Niu, Wang, Yang, Xu, & Qiao, ; Pedersen et al, ; Wang, Feng, Huang, Li, et al, ). However, this stands to be further improved to make use of hydrophobins in large‐scale applications feasible.…”
Section: Introductionmentioning
confidence: 99%
“…The hydrophobic patch on the surface of rHFBI comprises only a small part of the total surface area and the major part is hydrophilic. In addition, it was speculated that the measurement parameters for WCA data including the hydrophobin amount, the incubation temperature and time might affect the changes in WCA after modification of mica surfaces with rHFBI (Askolin et al 2006;Pedersen et al 2011;Qin et al 2007). Thus, the WCA data demonstrated that similar to the native HFBI, the rHFBI performed a unique amphiphile character that allowed them to self-assemble on siliconized glass and mica surfaces leading to the change of the wettability of rHFBI-coated solid substrates.…”
Section: Wca Measurementsmentioning
confidence: 99%
“…Class I hydrophobins including HGFI possess lower solubility in aqueous solution, therefore Class I hydrophobins have not been used as a tag for purification by now. Compared with Class II hydrophobins, Class I hydrophobin HGFI come from edible mushroom is considered safe and available because of its self-assembly and biocompatibility [6,[25][26][27] . However, there had been no study about fusing a bio-macromolecule with Class I hydrophobin before.…”
Section: Wca Measurement On Different Materials Surfacesmentioning
confidence: 99%